Baseline survey on psychosocial development of children ages 0-6 in E.C.D. and non-E.C.D. provinces - Ronquillo, Carolyn U. (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2004)
This research was part of the five-component Early Childhood Development (ECD) Special Nutrition Survey conducted in 2000. This comprehensive survey aimed to provide baseline information on nutrition, health, psychosocial, and care status, against which will be compared the endline information which have just been obtained in the 2003 Survey. This paper presents the baseline data on the psychosocial development of children age 0-6. An original tool, the Child Development Index (CDI) was constructed for this purpose. There were 21,383 respondents from seven Early Childhood Development (ECD) areas and nine non-ECD provinces, which were earlier identified as priority areas. Results determined the characteristic skills and ages in which the physical, cognitive, socio-emotional and personal-adaptive domains of development were attained. It was also noted that generally, ECD and non-ECD children attained developmental skills at about the same time, since no ECD intervention has yet been conducted at the time of the survey. In the full report, the information was useful in correlating the children's nutritional status with the psychosocial development and care-giving practices in early childhood. It is hoped that with these developmental norms derived, the governmental and non-governmental organizations and ECD practitioners would be greatly helped in developing programs and interventions to make these more developmentally-appropriate for the needs of the children.